DEVELOPING ENGLISH SPEAKING MATERIALS ABOUT FRONT OFFICE - Neneng Fahira Sudirman; Finny Anita; Maliqul Hafis (IKIP PGRI Pontianak, 2022)
This study aims to develop additional teaching material for XI grade students specializing in accommodation at SMKN 5 Pontianak. The instruments used in this study were a needs analysis questionnaire and an expert evaluation questionnaire. The step is to conduct a needs analysis by distributing questionnaires to students. The results of the needs analysis flow into the development of the module. . Developing the first draft of materials, consulting the first draft of materials to the experts, and revising and developing the final draft of materials. The data analysis was quantitatively analyzed using frequency and percentage, and the data obtained from the material evaluation were analyzed using descriptive statistics. Based on expert validation, this product is considered valid for student use. In summary, Front Office learning materials for class XI students majoring in hotel accommodation at SMKN 5 Pontianak have been successfully developed and can be used as complementary materials